Islamisasi Ilmu Dan Relevansi Sains-Agama Dalam Al-Qur’an Dan Hadis - Majid, Abd (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2018)
In the midst of Western science and technology hegemony over the societies of countries around the world, especially Muslims, has had an enormous influence on the style, style and worldview of society, and the most striking is the secularization of science, technology and religion. There is a paradigm that considers the dividing wall between science and religion (Islam). This has led to the impression that religious education runs without the support of science and technology, in contrast, public education is present without a religious touch. To overcome the situation, one of the things to do is to open and re-understand the text of the Qur'an and Hadith, and to establish a dialectic between science, technology, and the science of religion. In addition, the "Islamization of science" project is an alternative to the desecularetation of science and religious science, which seeks to integrate world problems with the hereafter, synthesize faith, science and charity, integrate dhikr with thought. In short, integrating transcendental values into aspects of worldly life including science and technology.